Analysis of welding time on microstructure, hardness, and torque of arc stud welding process - Amri, Moh. Syaiful; Mukhlis, Mukhlis; Ari, Muhammad; Wibowo, Alvalo Toto; Isworo, Annas Dwi (Journal of Welding Technology, 2024)
The manufacturing industry plays an important role in improving the national economy. One of the metal joining methods currently used is arc stud welding. Stud welding is used for welding bolts, which are useful for connecting parts in steel structures. This research was conducted with variations in current strength parameters of 200A, with welding times of 1, 2, and 3 seconds. The purpose of this research is to find the best parameters to determine the depth of penetration, heat-affected zone, and fusion zone of welding joints in A36 material. Macro testing results show that there are no defects such as cracks in the base metal, HAZ, or weld metal, meeting the ASME Sec. IX acceptance requirements. In addition, since the heat input remained within acceptable limits in the base metal areas of A36 and SS 304, the microtest results did not show significant changes. In the hardness test, the weld metal region obtained the highest value. The lowest average value was 192.85 HVN in the stud 1 specimen, while the highest average value was 195.37 HVN in the stud 3 specimen. The torque test shows that variations in welding time affect the torque strength; in specimen 3, it ranges from 50 Nm to 80 Nm.